Noncontrast myocardial T1 mapping using cardiovascular magnetic resonance for iron overload. Issue 6 (8th August 2014) - Sado, Daniel M.; Maestrini, Viviana; Piechnik, Stefan K.; Banypersad, Sanjay M.; White, Steven K.; Flett, Andrew S.; Robson, Matthew D.; Neubauer, Stefan; Ariti, Cono; Arai, Andrew; Kellman, Peter; Yamamura, Jin; et al.
<x xml:space="preserve">Abstract</x> Purpose To explore the use and reproducibility of magnetic resonance‐derived myocardial T1 mapping in patients with iron overload. Materials and Methods The research received ethics committee approval and all patients provided written informed consent. This was a prospective study of 88 patients and 67 healthy volunteers. Thirty‐five patients underwent repeat scanning for reproducibility. T1 mapping used the shortened modified Look–Locker inversion recovery sequence (ShMOLLI) with a second, confirmatory MOLLI sequence in the reproducibility group. T2* was performed using a commercially available sequence. The analysis of the T2* interstudy reproducibility data was performed by two different research groups using two different methods. Results Myocardial T1 was lower in patients than healthy volunteers (836 ± 138 msec vs. 968 ± 32 msec, P < 0.0001). Myocardial T1 correlated with T2* (R = 0.79, P < 0.0001). No patient with low T2* had normal T1, but 32% (n = 28) of cases characterized by a normal T2* had low myocardial T1. Interstudy reproducibility of either T1 sequence was significantly better than T2*, with the results suggesting that the use of T1 in clinical trials could decrease potential sample sizes by 7‐fold. Conclusion Myocardial T1 mapping is an alternative method for cardiac iron quantification. T1 mapping shows the potential for improved detection of mild iron loading. The superior reproducibility of T1 has potential implications for clinical trial design and therapeutic monitoring. J. Magn. Reson. Imaging 2015;41:1505–1511. © 2014 Wiley Periodicals, Inc.